Judicialização da Saúde e a efetivação do Direito Fundamental - Monsores, Ricardo Gomes (2018)
This paper aims to demonstrate and conceptualize the right to health as a right fundamental, the historical, social and political context by which passed, as well as identifies the social ills of each epoch. Expose themselves to division of fundamental rights into dimensions or generations, thereby demonstrating form the normative content of each and locating the dimension to which the right to health has been inserted at the international level. At national level we analyze the context history of public health in the country and its evolution to contemporary times, where the Unified Health System is located, how it was implemented and its implementation challenges. With some flaws in the system, we noticed the Health Judicialization phenomenon, being an outlet found by the SUS users / patients for the realization of their right to health. Yet, there are some negative reflexes in this social and legal phenomenon that will be analyzed and as well as procedural aspects of extreme relevance. THE The research methodology used in this work was bibliographic, deductive and qualitative. It is concluded that judicialization is a legitimate social movement and that the Judiciary is not usurping the competence of the other Powers, but judicialization does not extend fundamental rights, it restricts them in to the extent that mostly individual processes need to be of the money that should be passed on to public policies collective health In addition, most court proceedings use the emergency guardian institute to fulfill this requirement if right of extreme social relevance.